Toward digitalization futures in smallholder farming systems in Sub-Sahara Africa: A social practice proposal - Abdulai, Abdul-Rahim (Frontiers in Sustainable Food Systems, 2022)
This paper contributes to the digitalization of rural agriculture literature by proposing a social practice approach. Digitalization (practices) is conceived as an unfolding constellation of everyday farming activities manifested by practically conscious people meaningfully integrating materials elements of life. Thirty-one expert key informants' interviews were conducted with key informants on experiences and pathways for the future of digital agriculture in Africa. Thematic analysis of the interviews revealed that materials (access to digital tools, enabling digital infrastructure, supporting social infrastructure), competencies (digital literacy among farmers and extension officers, IT and data education among populaces), and meanings (connecting digitization with local customs and norms and aligning digital tools with the values/perceptions of what farming is) are critical elements to establishing and embedding digital tools and services in everyday agriculture in Africa. Thus, I propose adopting a social practice approach to understanding, researching, and guiding processes of rural smallholder digitalization. The proposed approach, the first application of the social practice lens to smallholder digitalization, would allow for interventions that focus on the building blocks that bring digitalization practices to life and provide an outlook to move beyond the technologies to equally value competencies and meanings in digital futures.